NUMERICAL ANALYSIS OF THE STRESS-STRAIN STATE OF THE MEMBRANE SHELL WITH ACCOUNT OF GEOMETRICAL NON-LINEARITY - S I Trushin; E V Sysoeva (Structural Mechanics of Engineering Constructions and Buildings, 2012)
The numerical procedures and results of analysis of rectangular membranes are presented. For the solution of the nonlinear problem the finite difference energy method and Newton-Raphson method are used.